Síndrome de Antón-Babinski (2020)
Antón syndrome is a neuropsychiatric syndrome which refers to cortical blindness combined with the denial of the visual deficit (anosognosia) that the patient is presenting and whose main characteristic is the collusion of the visual environment. Although several clinical cases of patients have been described over the years, the etiology of denial is still not clear, the damage has only been recognized in areas of association. The most common lesion associated with the syndrome is ischemia in the cerebral territory, specifically in the posterior cerebral arteries, although it should be taken into account that it has also occurred during some procedures or in the course of some pathologies. When the eye care professions make an exhaustive review, the absence of pathologies in the eyeball is evidenced that can explain the low visual perception of patients, for them it is important that they learn to identify the characteristic signs that may lead them to suspect the present syndrome during consultations.